2017
DOI: 10.1007/s12098-017-2403-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Scrub Typhus With and Without Meningitis

Abstract: Meningitis occurs in 15% of those with scrub typhus; those with meningitis have good neurological outcome with little mortality; those without meningitis have more complications and poorer outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…In the present study, cerebrospinal fluid protein level was significantly higher in the scrub typhus vs the non–scrub typhus group (110 vs 66.7). Other studies have reported moderately elevated protein, lymphocytosis, and normal glucose in the cerebrospinal fluid in scrub typhus meningoencephalitis, 8,18,19,30,32 although 1 study documented hypoglycorrhachia. 33 Longer duration of illness and elevated cerebrospinal fluid protein with lymphocytic pleocytosis makes tubercular meningitis the closest differential diagnosis in our setting.…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, cerebrospinal fluid protein level was significantly higher in the scrub typhus vs the non–scrub typhus group (110 vs 66.7). Other studies have reported moderately elevated protein, lymphocytosis, and normal glucose in the cerebrospinal fluid in scrub typhus meningoencephalitis, 8,18,19,30,32 although 1 study documented hypoglycorrhachia. 33 Longer duration of illness and elevated cerebrospinal fluid protein with lymphocytic pleocytosis makes tubercular meningitis the closest differential diagnosis in our setting.…”
Section: Discussionmentioning
confidence: 90%
“…Our findings were similar to other studies published in children from other parts of India. 5,7 Of various clinical features of meningitis, headache was noted in 62.5% and vomiting in 50% patients. Other pediatric studies have found headache in <50% children, though headache is seen in >60% of adults with STM.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria in this study were as follows: children using long-term medications, immunodeficiency, and have a chronic disease. Severity of the disease was defined based on previously published adult and pediatric studies (7)(8)(9)(10)(11)(12)(13). The study population was divided into two groups in terms of disease severity: (1) non-severe, patients without any complications and (2) severe, patients with severe complications.…”
Section: Methodsmentioning
confidence: 99%